Finite element analysis of mechanical stability of coarsened nanoporous gold. (1st April 2016) - Cho, Hoon-Hwe; Chen-Wiegart, Yu-chen Karen; Dunand, David C.
Abstract: The mechanical stability of nanoporous gold (np-Au) at various stages of thermal coarsening is studied via finite element analysis under volumetric compression using np-Au architectures imaged via X-ray nano-tomography. As the np-Au is coarsened thermally over ligament sizes ranging from 185 to 465 nm, the pore volume fraction is determinant for the mechanical stability of the coarsened np-Au, unlike the curvature and surface orientation of the ligaments. The computed Young's modulus and yield strength of the structures are compared with the Gibson–Ashby model. The geometry of the structures determines the locations where stress concentrations occur at the onset of yielding. Graphical abstract: